Analyzing farmers' preferences for substrate supply contracts for sugar beets - Saramena Sauthoff; Friederike Anastassiadis; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
Biogas production using biomass of agricultural origin plays a key role in Germany's energy transition process. Being the main substrate, maize has been increasingly criticized in recent years leading to a down-regulation of this crop for the use in biogas plants by an adjustment of the Renewable Energy Sources (RES) Act in 2012. Thus, it is necessary to widen the range of sustainable and suitable substrate alternatives. This study explores German farmers' willingness to grow sugar beets for biogas production based upon the analysis of a discrete choice experiment with 118 arable farmers conducted from November 2013 to February 2014. Models are estimated in willingness to pay space. Our results reveal that at least two-thirds of the participating farmers assess biogas production from sugar beets as an important and sustainable alternative to maize. However, with respect to their own farms, farmers prefer to maintain their status-quo instead of choosing a contract. Findings also indicate that risk-averse farmers are more likely to contract sugar beets as a biogas substrate than less risk-averse farmers resulting in a lower price demand. However risk-averse farmers prefer short contract periods and a small share of their arable land, otherwise they demand a markup. Regarding the expansion of renewable energies these findings are highly relevant for future political decisions that aim to enable a sustainable energy transition.
Keywords: 330; sugar beets; alternative biogas substrate; discrete choice experiment; supply contract design